The Joint Estimation of Term Structures and Credit Spreads - Patrick Houweling; Jaap Hoek; Frank Kleibergen (Tinbergen Institute, 1999)
We present a new framework for the joint estimation of the default-free government term structure and corporate credit spread curves. By using a data set of liquid, German mark denominated bonds, we show that this yields more realistic spreads than traditionally obtained spread curves that result from subtracting independently estimated government and corporate term structures. The obtained spread curves are smooth functions of time to maturity, as opposed to the twisting curves one gets from the traditional method, and are less sensitive to model specifications. To determine the `optimal' model specification, we use a newly developed test statistic that compares spread curves from competing models.
Keywords: G12; G13; C13; 330; Term structure estimation; Credit spreads; Corporate bonds; Splines; Zinsstruktur; Zinsstruktur; Deutschland